Penggunaan Fukujoshi Bakari dan Kurai Pada Kalimat Bahasa Jepang - Ningrum, Sandra setya; Astuti, Sri Puji; Rini, Elizabeth Ika Hesti Aprilia Nindya (Japanese Literature, 2015)
This research aims is to provide an explanation regarding fukujoshi bakari and kurai because the explanation from Japanese language textbooks are still lacking, it resulting in numerous errors in the use of fukujoshi bakari and kurai. To write this thesis, firstly, the author collected data, and then analyze the data, after that, the data presented in a descriptive form. Fukujoshi bakari and kurai in Indonesian language can be interpreted as ‘approximately’ or ‘around’, and it used to indicate an approximate. Although both fukujoshi have the same meaning, but both also have the difference. Fukujoshi bakari and kurai which attached to the noun have the same meaning, which are indicate the degree or level and indicate the quantity of approximate amount, timing, size and spacing. Fukujoshi bakari can’t replace each other while showing limited activity, describe something that has same level or degree with the exemplified, and when explain something which is taken for granted.   Keyword: fukujoshi bakari, fukujoshi kurai